The influence of the hand circulation on the assessment of venous distensibility of the human forearm with venous occlusion plethysmography - Burggraaf, Jacobus (Blackwell Science Inc, 2000)
AIMS: To determine the influence of the hand circulation on the determination of venous distensibility with venous occlusion plethysmography. METHODS: In a randomised study, duplicate measurements of forearm venous distensibility, with and without a wrist cuff, were made over occlusion periods of 3 and 12 min in eight volunteers. Treatments were compared with paired Student's t-tests and differences are presented as 95% confidence intervals (CI). Intra-subject variability was assessed with analysis of variance. RESULTS: Non-significant differences in increases in forearm volume between the occlusions with and without wrist cuff were found for the 3 min occlusion (CI: −0.4,+0.2%) and the 12 min occlusion period (CI: −0.7, +0.2%). However, the coefficient of variation was lower with the use of a wrist cuff; after 3 min occlusion (12% vs 19%) and after 12 min of occlusion (14% vs 24%). Forearm volume after 12 min of venous occlusion was 0.5% (CI:+0.4,+0.7) higher than after 3 min. CONCLUSIONS: Although venous distensibility was equal when assessed with and without wrist cuff, exclusion of the hand circulation reduces intraindividual variability. Equilibrium in forearm volume is not reached after 3 min period of venous occlusion, as often assumed. The magnitude of the additional increase after prolonged occlusion stresses the need for well-controlled studies.